(untitled) (Ciencias de la Ingeniería y Aplicadas, 2017)
The proposed design is based on the analysis of the operating parameters of the hydraulic rams for their optimal operation. The study carried out has allowed us to formulate the equations of the theoretical principle of the single-drive hydraulic ram and its experimental verification. The system of equations of the theoretical-experimental principle of the hydraulic ram was formulated considering the relationship between the variables: load volumetric flow, loss volumetric flow and pumping volumetric flow, loading and discharge height, flow ratio and number of strokes. per minute of the impulse valve. The impulse valve was modified using a check valve, where significant improvements in volumetric performance were obtained, reaching a maximum value of 72.24%; The number of blows varies between 77 and 99 blows per minute. The best working conditions were obtained for the volumetric flow value of 0.22 m3/h, corresponding to the discharge height of 2.8 m. An assessment was carried out considering the equivalent cost for 24 hours of work of the ram where the economic advantages of using the equipment for water pumping are indicated.